2020
DOI: 10.1073/pnas.2015440117
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of a liquid–liquid transition in an ab initio deep neural network model for water

Abstract: The possible existence of a metastable liquid–liquid transition (LLT) and a corresponding liquid–liquid critical point (LLCP) in supercooled liquid water remains a topic of much debate. An LLT has been rigorously proved in three empirically parametrized molecular models of water, and evidence consistent with an LLT has been reported for several other such models. In contrast, experimental proof of this phenomenon has been elusive due to rapid ice nucleation under deeply supercooled conditions. In this work, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 79 publications
(102 reference statements)
9
127
0
Order By: Relevance
“…3 D , Inset ). Such atomic force errors are similar or even smaller than those reported for other developed MLPs, e.g., for pure water ( 8 10 , 44 ). At the same time, the error estimate obtained for the AIMD configurations features essentially the same distance resolved profile, which reveals that our C-NNP simulations are able to conserve their predictive power, while substantially extending both time and length scales of the simulations.…”
Section: Reaching Longer Length and Time Scalessupporting
confidence: 85%
See 1 more Smart Citation
“…3 D , Inset ). Such atomic force errors are similar or even smaller than those reported for other developed MLPs, e.g., for pure water ( 8 10 , 44 ). At the same time, the error estimate obtained for the AIMD configurations features essentially the same distance resolved profile, which reveals that our C-NNP simulations are able to conserve their predictive power, while substantially extending both time and length scales of the simulations.…”
Section: Reaching Longer Length and Time Scalessupporting
confidence: 85%
“…In recent years, machine learning potentials (MLPs) have become a promising alternative, bypassing expensive ab initio calculations and extending length and time scales in molecular simulations ( 3 7 ). This is exemplified in studies on the understanding of the unique properties of water ( 8 10 ), structural and electronic transitions in disordered silicon ( 11 ), and phase transitions of hybrid perovskites ( 12 ) to name but a few. The success of MLPs is grounded in a number of distinct approaches that have been introduced over the years, notably, using artificial neural networks ( 13 17 ) or kernel-based methods ( 18 23 ).…”
mentioning
confidence: 99%
“…studied the isotope effects in liquid H 2 O and D 2 O using a deep neural network potential (NNP) trained on the SCAN functional. 35 A similar NNP was used to investigate the properties of supercooled water, 36 as well as the equilibrium between liquid water and ice Ih and Ic, 37 and the ice Ih/XI transition. 38 Building upon these previous studies, particularly the many-body analysis reported in ref 32, we provide here an assessment of the accuracy of the SCAN functional in predicting the properties of water.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, much work aimed at probing the phase behavior of supercooled water has been done via simulation 13 . Simulations of several classes of water models of varying accuracy and complexity have yielded evidence consistent with an LLT [24][25][26][27] . Some researchers have suggested the first-order-like transition between LDA and HDA provides evidence of the LLT in water, with LDA considered to be the structurally arrested analog of LDL and HDA the corresponding analog of HDL 5,28 .…”
mentioning
confidence: 98%